2014
DOI: 10.1159/000362340
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Functional Plasminogen in Eyes with Branch Retinal Vein Occlusion

Abstract: Purpose: To evaluate whether intravitreal functional plasminogen is elevated in eyes with branch retinal vein occlusion (BRVO) and to discover whether intravitreal plasminogen activities are correlated with the extent of blood-retina barrier (BRB) breakdown. Methods: Our study is a prospective case series of 20 consecutive patients with BRVO and 10 consecutive patients serving as controls. Vitreous taps were extracted from the central vitreous body and plasminogen was functionally determined in an innovative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…; Bertelmann et al. , ,b,c, ). For patient management, it is of notably importance to distinguish between ischaemic‐ and non‐ischaemic‐typed RVO, because the ischaemic variant can cause severe and irreversible damage to the eye (Rogers et al.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…; Bertelmann et al. , ,b,c, ). For patient management, it is of notably importance to distinguish between ischaemic‐ and non‐ischaemic‐typed RVO, because the ischaemic variant can cause severe and irreversible damage to the eye (Rogers et al.…”
Section: Discussionmentioning
confidence: 94%
“…; Bertelmann et al. , ,b,c, ) could be of benefit to hamper neovascular intricacies. Whereas ppV is an invasive surgical procedure (Tachi et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bertelmann et al (2014) recently found functional plasminogen to be 6e7 fold higher in vitreous taps from patients with BRVO compared to controls. The study also identified intravitreal functional plasminogen to correlate with VEGF.…”
Section: Blood Coagulationmentioning
confidence: 96%